Guidance for the occupational medicine service regarding the prevention of hepatitis C and HIV infection in Poland - Andrzej Marcinkiewicz; Jolanta Walusiak-Skorupa; Paweł Wdówik; Dorota Zarębska-Michaluk; Małgorzata Inglot; Magdalena Władysiuk; Tomasz Jan Prycel; Robert Flisiak (Medycyna Pracy)
The set up of new healthcare models by taking into account diagnosis and health education of the viral infection, aims to achieve the goals of the World Health Organization Global Health Sector Strategy on viral diseases for 2022–2030. In comparison to Europe, Poland is ranked among countries with an moderate prevalence of hepatitis B and C virus (HBV and HCV), also human immunodeficiency virus (HIV). An additional challenge is the changing epidemiological situation due to the impact of immigrants, resulting mainly from the war in Ukraine. The article presents current guidance for HCV and HIV diagnosis and presents the role of occupational health service (OHS) for primary and secondary prevention of the infectious diseases. It was considered to expand the scope of periodic examinations to include diagnosis of HBV, HCV and HIV infections among health care workers, who have not had it performed so far. In the case of abnormal level of alanine aminotransferase (ALT), aspartate aminotransferase (AST) or γ-glutamyl transpeptidase (GGT) found during routine pre-employment or periodic examinations for specific occupational exposures and it is considered crucial to implement further measures to exclude or confirm HBV or HCV infection, with indications for further management in primary care, and followed by subsequent periodic examinations. The need to pay attention to any symptoms that may indicate HBV, HCV and/or HIV infection, to perform additional diagnostic tests (e.g., point of care), and to determine the next steps in case of positive result was indicated. It emphasized the need to tailor the delivery of information to the patient, including taking care to ensure that immigrants’ workers understand the next steps. It was recommended that the OHS conduct educational activities to raise health awareness of HIV, HCV, HBV infections, both through health policy programs as well as through broader activities in cooperation with the employer. Med Pr Work Health Saf. 2024;75(5):485–494